2019
DOI: 10.1186/s12935-019-0755-8
|View full text |Cite
|
Sign up to set email alerts
|

FOXD3 may be a new cellular target biomarker as a hypermethylation gene in human ovarian cancer

Abstract: Background FOXD3 is aberrantly regulated in several tumors, but its underlying mechanisms in ovarian cancer (OC) remains largely unknown. The present study aimed to explore the role and associated mechanisms of FOXD3 in OC. Methods Microarray data from GEO was used to analyze differential CpG sites and differentially methylated regions (DMR) in tumor tissues and Illumina 450 genome-wide methylation data was employed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Another finding suggests that promoter methylation of RASSF1A, APC, GSTP1, and MGMT correlates with the presence of invasive ovarian carcinomas (Makarla et al, 2005). Hypermethylation of FOXD3 correlated with tumor suppressive role (inhibition of proliferation, migration and promotion of apoptosis) in ovarian cancer cells and thus could serve as a potential therapeutic target for diagnosis of ovarian cancer (Luo et al, 2019).…”
Section: Tissue Biomarkers Diagnosismentioning
confidence: 97%
“…Another finding suggests that promoter methylation of RASSF1A, APC, GSTP1, and MGMT correlates with the presence of invasive ovarian carcinomas (Makarla et al, 2005). Hypermethylation of FOXD3 correlated with tumor suppressive role (inhibition of proliferation, migration and promotion of apoptosis) in ovarian cancer cells and thus could serve as a potential therapeutic target for diagnosis of ovarian cancer (Luo et al, 2019).…”
Section: Tissue Biomarkers Diagnosismentioning
confidence: 97%
“…Initial results indicated that overexpression of FOXD3 could promote the apoptosis while inhibiting the proliferation and chemoresistance of OC cells. FOXD3 is poorly expressed in OC tissues while its overexpression weakens OC cell proliferating and migrating ability and increases cell apoptosis while restraining tumor growth in vivo [ 17 ]. FOXD3 expression is downregulated in CP-resistant nasopharyngeal carcinoma cells and it can promote the expression of miR-26b which sensitizes nasopharyngeal carcinoma cells to CP [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chordate embryonic development (FOXD3, WT1, BRCA1, and BRCA2) was enriched in DEGs in the ovaries. Demethylated FOXD3 decreases cell migration and proliferation abilities and increases cell apoptosis, even in ovarian cancer [ 36 ]. FOXD3 was more lowly expressed in FM_1 potentially contributing to accelerated cell aging, while the other three genes were higher expressed in FM_1.…”
Section: Discussionmentioning
confidence: 99%